Application of CT pulmonary angiography and echocardiography in acute pulmonary embolism: A cross‐sectional study - Mozhgan Sametzadeh; Sahar Dadgostar; Mohammad Ghasem Hanafi; Mohammad Mohammadi (Health Science Reports, 2023)
Abstract Background Pulmonary Embolism (PE) is an acute and potentially fatal condition defined as the blockage of pulmonary arteries by an embolism that can be from various origins. Objective The present study aimed to investigate the findings of computed tomography pulmonary angiography (CTPA) and echocardiography in patients with acute PE. Methods The present cross‐sectional study included some patients with clinical manifestations of PE who underwent CTPA and echocardiography. The radiologic findings, PE severity, and outcome of the patients were recorded. Moreover, echocardiography was performed by an expert cardiologist using a high‐resolution device, while CTPA was performed by an expert radiologist using a 16‐slice device and a two‐step selective test bolus method. Results According to our findings, a total number of 147 patients were diagnosed with PE, including 44 (29.93%), 44 (29.93%), and 59 (40.14%) cases of mild, moderate, and severe PE, respectively. Moreover, 25 patients (17%) finally expired due to PE. Regarding the CTPA findings, 31 patients (21.1%) had septum flattening, while 35 (23.8%) had a septum deviation toward the left ventricle. Also, there were significant correlations between mortality and some CTPA findings, including severe PE (p < 0.001), the presence of septal deviation (p = 0.007), and higher diameters of the main pulmonary artery (p < 0.001) and right ventricle (p = 0.008). Conclusion CTPA is a valid and accessible modality for diagnosing and evaluating PE in suspected patients. Moreover, several findings in CTPA could predict adverse outcomes, such as death, in patients with PE.